14 Years longitudinal evaluation of clinical information systems acceptance: The HEGP case. (February 2016) - Hadji, Brahim; Martin, Guillaume; Dupuis, Isabelle; Campoy, Eric; Degoulet, Patrice
Highlights: To our knowledge this is the first longitudinal, multi-professional acceptance evaluation of a fully deployed and integrated CIS. Acceptance models should be adapted to the state of deployment of a CIS. In late adoption phases of a comprehensive CIS deployment, a continuance intention dimension should be added in evaluation models. Disappearance of the positive bilateral relationship between use and satisfaction could be in the long run considered as a CIS success indicator. Abstract: Context: Meaningful use and end-user satisfaction are two major components of the success of a clinical information system (CIS). The purpose of this study was to longitudinally measure and analyze the CIS use and satisfaction determinants in a multi-professional group at the Georges Pompidou university hospital (HEGP) in Paris. Methods: From the different evaluation surveys performed at HEGP, three periods were considered corresponding to 4, 8 and over 10 years after the first CIS deployment in 2000, respectively. Six acceptance dimensions were considered: CIS quality (CISQ), facilitating conditions (FC), perceived usefulness (PU), confirmation of expectations (CE), use, and global satisfaction (GS). Relationships between these constructs were tested through multiple regressions analysis and structural equation modeling (SEM). Results: Responses were obtained from 298, 332, and 448 users for the three periods considered. CIS acceptance dimensions progressively and significantly increased over time. Significant differences between professions were observed with an initial low PU among medical staff. In the early deployment phase, GS appeared to be determined by CIS use, CISQ and PU ( R 2  = .53 in SEM). In the very late post-adoption phase, GS was strongly determined by CISQ, CE, and PU ( R 2  = .86 in SEM) and was no longer associated with CIS use. Conclusion: Acceptance models should be adapted to the phase of deployment of a CIS and integrate end-users' individual characteristics. Progressive reduction over time of the positive relationships between CIS use and satisfaction could possibly be considered as a maturity indicator of CIS deployment. These observations validate the introduction in post-adoption models of a continuance intention dimension.